Linking current dental education to gerontological education to meet the oral health needs of growing aging populations - Tabrizi, Maryam; Lee, Wei-Chen (Frontiers in Oral Health, 2023)
Objective: This study aimed to recognize the gaps in dental education by studying the current level of geriatric oral health training of recent graduated dentists who have been admitted into an Advanced Education in General Dentistry (AEGD) program. Methods: The AEGD program was developed along with the Age-Friendly 4Ms model to enhance current dental education. We adopted the Rapid Cycle Quality Improvement model to test the effectiveness of the training for AEGD residents from 2019 to 2022. A total of 18 residents participated (6 residents each year). A 5-question survey was administered before and after the rotation and Wilcoxon signed-rank with Fisher Exact tests were conducted to compare pre-and postrotation results. Results: All 18 residents have completed pre-and post-program surveys. They self-reported minimal to no training in preparation to provide care to older adults with multiple chronic conditions. After the rotation, residents' confidence in treating older adults was significantly increased (p=0.011). Meanwhile, residents gained knowledge to apply the 4Ms framework (what matters, medication, mentation, and mobility) to their practices (p=0.015) and provide age-friendly care for older adults.The study identified and addressed the missing link in dental education to gerontological and geriatrics education. More clinical rotations and didactic training to equip residents with competences of providing geriatric oral health are strongly recommended.